Assessment instruments of professional competence in nursing: an integrative review (Research, Society and Development, 2022)
The objective of this article is to know the instruments and methods for the assessment of professional competence in nursing described in the scientific production. This is an integrative literature review, through research in the Virtual Health Library and in the Portal of Periodicals of the Coordination for the Improvement of Higher Education Personnel, with three controlled terms, “professional competence”, “nursing” and “education”; and two uncontrolled: “concepts” and “assessment”. 12 articles published between 2007 and 2018 were analyzed. Each study presented an instrument and method for evaluating professional competence. It was observed that the focus of the evaluation was centered on theoretical knowledge and professional competence, without evaluating the professional attitude, even when referring to employing psychometric and holistic methodologies. There was little exploration of the repercussion of transculturality and socioeconomic-cultural aspects in these assessments, which may affect the assessment of the nursing team’s competences, especially regarding the assessment of professional attitude.